Periodontal ligament, cementum, and alveolar bone in the oldest herbivorous tetrapods, and their evolutionary significance. - Aaron R H LeBlanc (Public Library of Science (PLoS), 2013)
Tooth implantation provides important phylogenetic and functional information about the dentitions of amniotes. Traditionally, only mammals and crocodilians have been considered truly thecodont, because their tooth roots are coated in layers of cementum for anchorage of the periodontal ligament, which is in turn attached to the bone lining the alveolus, the alveolar bone. The histological properties and developmental origins of these three periodontal tissues have been studied extensively in mammals and crocodilians, but the identities of the periodontal tissues in other amniotes remain poorly studied. Early work on dental histology of basal amniotes concluded that most possess a simplified tooth attachment in which the tooth root is ankylosed to a pedestal composed of "bone of attachment", which is in turn fused to the jaw. More recent studies have concluded that stereotypically thecodont tissues are also present in non-mammalian, non-crocodilian amniotes, but these studies were limited to crown groups or secondarily aquatic reptiles. As the sister group to Amniota, and the first tetrapods to exhibit dental occlusion, diadectids are the ideal candidates for studies of dental evolution among terrestrial vertebrates because they can be used to test hypotheses of development and homology in deep time. Our study of Permo-Carboniferous diadectid tetrapod teeth and dental tissues reveal the presence of two types of cementum, periodontal ligament, and alveolar bone, and therefore the earliest record of true thecodonty in a tetrapod. These discoveries in a stem amniote allow us to hypothesize that the ability to produce the tissues that characterize thecodonty in mammals and crocodilians is very ancient and plesiomorphic for Amniota. Consequently, all other forms of tooth implantation in crown amniotes are derived arrangements of one or more of these periodontal tissues and not simply ankylosis of teeth to the jaw by plesiomorphically retaining "bone of attachment", as previously suggested.